Good social skills despite poor theory of mind: exploring compensation in autism spectrum disorder. (26th March 2018) - Livingston, Lucy Anne; Colvert, Emma; ,; Bolton, Patrick; Happé, Francesca
Abstract : Background: It is proposed that some individuals with Autism Spectrum Disorder (ASD) can 'compensate' for their underlying difficulties (e.g. in theory of mind; ToM), thus demonstrating relatively few behavioural symptoms, despite continued core cognitive deficits. The mechanisms underpinning compensation are largely unexplored, as is its potential impact on mental health. This study aimed to estimate compensation patterns in ASD, by contrasting overt social behaviour with ToM task performance, in order to compare the characteristics of 'Low' and 'High' Compensators. Methods: A total of 136 autistic adolescents, from the ongoing Social Relationships Study, completed a range of cognitive tasks, the Autistic Diagnostic Observation Schedule (ADOS) and a self‐report anxiety questionnaire. Participants were assigned compensation group status; High Compensators demonstrated good ADOS scores despite poor ToM performance, while Low Compensators demonstrated similarly poor ToM, accompanied by poor ADOS scores. Results: High Compensators demonstrated better IQ and executive function (EF), but greater self‐reported anxiety, compared with Low Compensators. Such differences were not found when comparing individuals who had good versus poor ADOS scores, when ToM performance was good. Other core autistic characteristics (weak central coherence, nonsocial symptoms) did not differentiate the High and Low Compensators. Conclusions: IQ, EF and anxiety appear to be implicated in the processes by which certain autistic young people can compensate for their underlying ToM difficulties. This tendency to compensate does not appear to reflect the severity of 'hit' for ASD per se, suggesting that well‐compensated individuals are not experiencing a milder form of ASD. The construct of compensation in ASD has implications for research and clinical practice. Abstract : Read the Commentary on this article at doi:10.1111/jcpp.12989